2016
DOI: 10.3171/2015.4.jns141833
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics for rapid detection of isocitrate dehydrogenase 1 mutation for intraoperative application

Abstract: S equence analysis of glioblastoma found a mutation in isocitrate dehydrogenase 1 (IDH1), which mostly resulted in the replacement of wild-type arginine in position 132 with histidine (R132H). 25 Studies have reported that the IDH1 mutation is frequently detected in diffuse astrocytoma (59%-88%), anaplastic astrocytoma (52%-78%), oligodendroglioma (68%-82%), anaplastic oligodendroglioma (60%-75%), oligoastrocytoma (50%-94%), anaplastic oligoastrocytoma (66.1%-78%), and secondary glioblastomas (50%-88%), but ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…High-resolution melting is easy, fast and sensible, while it requires high quality for RT-PCR amplifier and operator 22 . There are also many detection methods for targeting 2-HG, such as the downstream metabolites of IDH-mut, including magnetic resonance spectroscopy (MRS) 23 , multiple mass spectrometry (MS) [24][25][26] and microfluidics 27 . Among them, MS is relatively mature and can quickly and accurately detect IDH mutation in surgery, which is relying on expensive mass spectrometers.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution melting is easy, fast and sensible, while it requires high quality for RT-PCR amplifier and operator 22 . There are also many detection methods for targeting 2-HG, such as the downstream metabolites of IDH-mut, including magnetic resonance spectroscopy (MRS) 23 , multiple mass spectrometry (MS) [24][25][26] and microfluidics 27 . Among them, MS is relatively mature and can quickly and accurately detect IDH mutation in surgery, which is relying on expensive mass spectrometers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports on intervertebral disc disease suggest that up to 75% of the underlying etiology is attributed to genes. [ 44 ] Other diseases of neurosurgical importance found to have a component of genetic etiology include gliomas,[ 9 48 ] schwannomas,[ 24 ] meningiomas,[ 12 ] intracranial aneurysms,[ 26 38 72 73 ] arteriovenous malformations,[ 19 ] cavernous malformations,[ 21 ] subarachnoid hemorrhage,[ 25 ] idiopathic scoliosis,[ 22 ] moya-moya disease,[ 27 ] hemorrhagic, and ischemic strokes. The results generated from these genome wide association (GWA) studies, revealing specific SNPs and their association with disease, are the stepping stones for better understanding of disease risk, prediction, treatment, and prognosis.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have reiterated the utility of maximal tumor removal on both progression free as well as overall survival (OS) in p-GBM (4, 9, 10, 13, 14, 51). The Children' s Cancer Group (CCG) study-945 showed that children with HGG who underwent a surgical resection of 90% or greater had a progression-free survival (PFS) of 35 ± 7% as compared with a 5-year PFS of 17 ± 4% in patients who did not (50,51). Reporting on probably the largest single-center experience of p-GBM, we have also shown that the extent of tumor excision was a strong predictor of long progression-free survival as well as OS (4).…”
Section: Management Surgerymentioning
confidence: 99%
“…These advanced techniques include intraoperative neuronavigation, intraoperative ultrasound, intraoperative MRI, intraoperative cortical mapping, etc. Recent technological advances utilizing microfluidic chips allow for rapid analysis of the operative specimen for molecular signatures like IDH mutation within no time (51,52). Therefore, it is possible now to make a molecular diagnosis even intraoperatively.…”
Section: Management Surgerymentioning
confidence: 99%